Dreams of Savannah - White, Roseanna M. (Bethany House, 2021)
"1861. When she receives word that her sweetheart has been lost during a raid on a Yankee vessel, Cordelia Owens clings to hope and comes up with many a romantic tale of his eventual homecoming to reassure his mother and sister. But Phineas Dunn finds nothing redemptive in the first horrors of war. Struggling for months to make it home alive, he returns to Savannah injured and cynical, and all too sure that he is not the hero Cordelia seems determined to make him. When Fort Pulaski falls and the future wavers, they both must decide where the dreams of a new America will take them, and if they will go together."--Provided by publisher.